Expression of proteins in superior and inferior spikelets of rice during grain filling under different irrigation regimes. Issue 1 (30th November 2015) - Chen, Tingting; Xu, Genwen; Wang, Zhiqin; Zhang, Hao; Yang, Jianchang; Zhang, Jianhua
Abstract : Poor grain filling of later‐flowering inferior spikelets is a serious problem in modern rice cultivars, but the reason and regulation remain unclear. This study investigated post‐anthesis protein expression in relation with grain filling and the possibility to use irrigation methods to enhance grain filling through regulating protein expression. One japonica rice cultivar was field‐grown under three irrigation treatments imposed during the grain filling period: alternate wetting and moderate soil‐drying (WMD), alternate wetting and severe soil‐drying (WSD), and conventional irrigation. High resolution 2DE, combined with MALDI/TOF, was used to compare differential protein expression between superior and inferior spikelets. Results showed that the expression of proteins that function in photosynthesis, carbohydrate and energy metabolism, amino acids metabolism and defense responses were largely down‐regulated in inferior spikelets compared to those in superior spikelets. The WMD treatment enhanced grain filling rate and the expression of these proteins, whereas the WSD treatment decreased them. Similar results were observed for transcript levels of the genes encoding these proteins. These results suggest that down‐regulated expression of the proteins associated with grain filling contribute to the poor grain filling of inferior spikelets, and post‐anthesis WMD could improve grain filling through regulating protein expression in the spikelets.